Pengaruh Budaya Organisasi, Stres Kerja Dan Pemberian Kompensasi Terhadap Kinerja Karyawan Di Lisa Catering Semarang - Jumria Umasugi; Kiswoyo Kiswoyo (CV. Ulil Albab Corp, 2024)
This study aims to analyze the influence of Organizational Culture, Job Stress and Compensation on Employee Performance. This study uses primary data obtained from questionnaires. The population in this study were employees of Lisa Catering Semarang and a sample of 44 respondents was obtained using the solve method. Data collection method by distributing questionnaires. Hypothesis testing using intervening multiple regression analysis with SPSS 25.0 software. The results showed that the Organizational Culture variable had a positive and significant effect on Employee Performance, Job Stress had a positive and significant effect on Employee Performance, and Compensation had a positive and significant effect on Employee Performance.